Variation in the concentration and indexing black pepper plants for PYMoV and CMV through DAS-ELISA - C K Thankamani, P A Mathew, V Bhadramurthy, A I Bhat, Jasmine George (Journal of Spices and Aromatic Crops, 2008)
Variation in concentration of Piper yellow mottle virus (PYMoV) and Cucumber mosaicvirus (CMV) in stunted disease infected black pepper plants from different varieties/cultivarsduring different months of a year was studied by DAS-ELISA. Higher A405 values wererecorded from October to February in four varieties/cultivars of black pepper tested andPanniyur-1 had the highest concentration of both the viruses. Results on distribution ofthe viruses within a plant from three varieties/cultivars showed that young leaf containedhighest concentration of both the viruses while root region recorded the least. A total of2186 black pepper nursery plants from eleven varieties were indexed by DAS-ELISA for thepresence of viruses. Of these, 714 plants were found infected with either of the two viruses.Among these, IISR-Sreekara had the highest number of infected plants followed by IISR-Subhakara while Panniyur-5 had the least number of infected plants. Of the 714 plantstested positive, 390 plants exhibited no visible external symptoms indicating the necessityfor sensitive diagnosis in identifying virus-free planting material.